2016
DOI: 10.1111/1753-0407.12361
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Western and Asian type 2 diabetes patients in the incidence of vascular complications and mortality: A systematic review of randomized controlled trials on lowering blood glucose

Abstract: Background: Differences exist between Western and Asian people with type 2 diabetes (T2D). The aim of the present systematic review was to determine whether there are differences in chronic diabetic vascular complications (CDVCs) and mortality between Western and Asian patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Firstly, compared with their Western counterparts, Asian individuals might have a different pattern for complications of diabetes 42. A meta-analysis of interventional randomised controlled trials showed that the risk of microvascular events and new or worsening nephropathy was significantly higher in Asian patients than in western patients 43. In our analysis, the risk of macrovascular disease (composite cardiovascular disease, coronary heart disease, and stroke) associated with prediabetes was similar in Asian and non-Asian patients.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Firstly, compared with their Western counterparts, Asian individuals might have a different pattern for complications of diabetes 42. A meta-analysis of interventional randomised controlled trials showed that the risk of microvascular events and new or worsening nephropathy was significantly higher in Asian patients than in western patients 43. In our analysis, the risk of macrovascular disease (composite cardiovascular disease, coronary heart disease, and stroke) associated with prediabetes was similar in Asian and non-Asian patients.…”
Section: Discussionmentioning
confidence: 58%
“…Secondly, differences in genetics, socioeconomic factors, and treatment approaches for atherosclerotic cardiovascular disease between Asia and other continents might also have a role in the influence of prediabetes on mortality in Asia 4346. Based on these results, prediabetes management programmes, tailored to Asian patients with atherosclerotic cardiovascular disease, might be clinically important, and these programmes should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are differences on weight outcomes and weight gain liabilities on FEP patients from Western countries as opposed to patients from Asian countries (Tek et al, 2016). Previous studies has also shown differences in prevalence of type II diabetes and in glucose metabolism outcomes between different ethnicities (Li, Dong, Wu, & Tong, 2016;Whiting, Guariguata, Weil, & Shaw, 2011). Therefore, we also performed a sub-group analysis to compare glucose metabolism outcomes between different regions (Asian vs non-Asian).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Differences in BG profiles among patients with T2DM of different races and ethnicities may have implications for how T2DM is managed and for treatment outcomes. Patients in Asia have earlier onset and longer duration of T2DM and are at a higher risk of microvascular complications, particularly renal disease, compared with Caucasians . Analysis of BG profiles among Caucasian patients with T2DM who were insulin‐naive has shown that the contribution of postprandial BG to excess hyperglycemia decreases relative to fasting BG in poorly controlled patients .…”
Section: Discussionmentioning
confidence: 99%